STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN PROGRAM SEKOLAH BERBASIS SEMI PESANTREN DI UPTD SDN 360 ANABANUA KECAMATAN MANIANGPAJO KABUPATEN WAJO - Rahmawati; Syamsiar; Besse Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the leadership strategies of school principals in developing semi-pesantren-based school programs at UPTD SDN 360 Anabanua, Maniangpajo District, Wajo Regency. The study uses a qualitative approach with a case study type to gain an in-depth understanding of the processes, meanings, and social dynamics that occur in the implementation of the program. Data collection techniques were carried out through interviews, documentation, and observation. The results of the study show that the principal's leadership strategy in developing the semi-pesantren program was implemented through the stages of planning, organizing, implementing, and evaluating in a participatory manner by involving various parties in the school environment. The semi-boarding school program was integrated with the national curriculum through the habit of religious values such as praying together, reading the Qur'an, praying in congregation, morning zikir, and memorizing Juz 30. The implementation of the program was also supported by the exemplary behavior of the principal, the cooperation of teachers, and the involvement of parents and the school committee. However, there are several obstacles in its implementation, such as limited facilities and infrastructure, the quality of human resources, and limited learning time. Overall, the principal's participatory, transformational, and collaborative leadership strategies have been able to support the successful development of the semi-boarding school-based program in shaping the religious character of students.